ANALISIS PENERIMAAN PAJAK DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN KUTAI BARAT - Albina, Maskan, dan Frendly Albertus (Prodi Ilmu Administrasi Negara, 2020)
This study aims to find out how much influence the local tax collectionsystem has on local revenue. The independent variable used in this study isthe regional tax collection system and the dependent variable is localrevenue. This research was conducted at the West Kutai District Governmentprecisely at the Office of the Regional Revenue Agency of West KutaiRegency , located in the city of Barong Tongkok . The method used isdescriptive qualitative method. The results of the study indicate that thesystem of collecting local taxes and levies by the Government of West KutaiRegencyhave not shown satisfactory results. Many taxpayers are difficult topay taxes. It can also be seen from the contribution of regional taxesindicating that the West Kutai District has not been able to carry outregional autonomy consequently because it still depends on other revenuesoutside of revenues from Regional Original Revenue. From the Tax RevenueSystem and regional levies to the West Kutai District Government, it uses awith holding system for each type of regional tax where using this systemmakes it easier for local governments to carry out local tax revenues . In thisstudy, the authors also suggest some things that may be input to theGovernment of the district of Kutai Barat in at enhancing the acceptance ofPAD in particular on post tax and levies area .